Toxic Masculinity Patriarki Dalam Novel Perempuan Yang Menangis Kepada Bulan Hitam Karya Dian Purnomo - Imani, Putri Revi Puja; Murniviyanti, Liza; Armariena, Dian Nuzulia (Institut Teknologi Pendidikan Indonesia, 2023)
Toxic Masculinity appears in the social construction of a patriarchal society where a man's masculinity is based on repressive behavior and must act dominantly. These men also givecertain expectations in the context of gender studies, Toxic Masculinity is one of the factorssymbolizing patriarchy in society because men will always give expectations that are the main leaders, and also exist in other Toxic Masculinities because of that research This study aims to find out the location of Toxic Masculinity Patriarchy in Dian Purnomo's Novel Women Crying To The Black Moon. The benefits of this research are expected to be able to provide references, knowledge, and references especially in Toxic Masculinity Patriarchy, in the novel Woman Crying for the Black Moon by Dian Purnomo. The research method used is a qualitative descriptive method. The source of data in this research is The Novel Who Cried for the Black Moon. The data collection technique is a data source triangulation technique. The data analysis technique used is reading and thorough and accurate, making a synopsis of the Novel Woman Crying for the Black Moon by Dian Purnomo, Analyzing and recordingdata The research results in the novel Woman Crying for the Black Moon show that ToxicMasculinity towards women is divided into three, namely acts of violence against women. Inthe forms of resistance of the characters as a form of existence, three forms are found, namely working hard, understanding cases of harassment of women, and making arrest strategies. perpetrator.